Decomposability of lichens and bryophytes from across an elevational gradient under standardized conditions. Issue 9 (12th June 2020) - van Zuijlen, Kristel; Roos, Ruben E.; Klanderud, Kari; Lang, Simone I.; Wardle, David A.; Asplund, Johan
Abstract : Lichens and bryophytes are abundant primary producers in high latitude and high elevation ecosystems, and they play an important role in ecosystem processes such as decomposition and nutrient cycling. Despite their importance, little is known about the decomposability of lichens and bryophytes either among or within species, at the whole community level, or how this decomposability is affected by their functional traits. Here, we studied decomposability of lichens and bryophytes at the community‐level and individual species‐level (using 21 species and genera) collected from an elevational gradient in alpine Norway. In order to isolate the elevation effect on litter quality, we used a standardized laboratory bioassay to measure decomposability. In contrast to our expectations, we found that community‐level decomposability of lichens and bryophytes increased with elevation and thus decreasing temperature. In contrast, phosphorus release from the litter decreased with elevation while nitrogen release was unresponsive. Decomposability was explained by nutrient concentrations, litter pH and primary producer group identity (lichens versus bryophytes) at both the individual species and community levels. Species turnover (changes in species composition and abundance) was the main driver of decomposability across elevation at the community level, despite some of the traits explaining decomposability showing high intraspecific variability. Our study highlights the importance of among‐species variation in determining lichen and bryophyte decomposability. Further, the higher decomposability that we found for higher elevations suggests that global warming might result in a shift towards slower decomposable lichen and bryophyte species.